Anchoring the experts: Using vignettes to compare party ideology across countries. (23rd October 2014) - Bakker, Ryan; Edwards, Erica; Jolly, Seth; Polk, Jonathan; Rovny, Jan; Steenbergen, Marco
Expert surveys are a valuable, commonly used instrument to measure party positions. Some critics question the cross-national comparability of these measures, though, suggesting that experts may lack a common anchor for fundamental concepts such as economic left–right. Using anchoring vignettes in the 2010 Chapel Hill Expert Survey, we examine the extent of cross-national difference in expert ideological placements. We find limited evidence of cross-national differences; on the whole, our findings further establish expert surveys as a rigorous instrument for measuring party positions in a cross-national context.